Debye-scale solitary structures in the Martian magnetosheath - Kakad, Bharati; Kakad, Amar; Aravindakshan, Harikrishnan; Kourakis, Ioannis (My University, 2022)
We present an analysis of 450 solitary wave pulses observed by the Langmuir Probe and Waves instrument on the Mars Atmosphere and Volatile EvolutioN spacecraft during its five passes around Mars on 2015 February 9. The magnitude and duration of these pulses vary between 1 and 25 mV m−1 and 0.2–1.7 ms, respectively. The ambient plasma conditions suggest that these pulses are quasi-parallel to the ambient magnetic field and can be considered electrostatic. These pulses are dominantly seen in the dawn (5–6 LT) and afternoon-dusk (15–18 LT) sectors at an altitude of 1000–3500 km. The frequencies of these electric field pulses are close to the ion plasma frequency (i.e., fpi ≤ fef ≪ fpe), which suggests that their formation is governed by ion dynamics. The computer simulation performed for the Martian magnetosheath plasma hints that these pulses are ion-acoustic solitary waves generated by drifted ion and electron populations and their spatial scales are in the range of few ion Debye lengths (1.65–10λdi). This is the first study to report and model solitary wave structures in the Martian magnetosheath.
Keywords: Mars; Martian magnetosheath; Debye-scale; Planetary magnetosphere; Space plasma